Umbilical Cord-Derived Mesenchymal Stem Cells Attenuate S100-Induced Autoimmune Hepatitis via Modulating Th1 and Th17 Cell Responses in Mice - Xiaofeng Wei; Xinhong Cheng; Yang Luo; Xun Li (Stem Cells International)
Currently, the first-line treatment for autoimmune hepatitis (AIH) is still the combination of glucocorticoids or immunosuppressants. However, hormone and immunosuppressive therapy can cause serious side effects, such as Cushing syndrome and bone marrow suppression. Previous studies reported on the applicability and safety of mesenchymal stem cells (MSCs) to ameliorate liver inflammation and fibrosis. However, the characteristics of MSCs sources directly contribute to the different conclusions on the mechanisms underlying MSC-mediated immunoregulation. Bone marrow-derived MSCs can exert an immunosuppression effect to ameliorate the S100-induced AIH model by inhibiting several proinflammatory cytokines and upregulating of PD-L1 in liver tissue. It is not clear whether human umbilical cord-derived MSCs (hUC-MSCs) could directly inhibit liver inflammation and ultimately alleviate the dysfunction of hepatocytes in the AIH model. First, hUC-MSCs were extracted from umbilical cord tissue, and the basic biological properties and multilineage differentiation potential were examined. Second, 1 × 106 hUC-MSCs were administered intravenously to AIH mice. At the peak of the disease, serum levels of alanine aminotransferase and aspartate aminotransferase and pathologic damage to liver tissue were measured to evaluate liver function and degree of inflammation. We also observed that the infiltration of CD4+ T cells in the liver was significantly reduced. Furthermore, the frequency of the splenic IFNγ- and IL-17A- producing CD4+ T cells were also significantly decreased, while we only observed an increasing trend in Treg cells in liver tissue. Third, an RNA sequencing analysis of liver tissue was performed, which showed that in the UC-MSC-treated group, the transcriptional profiles of inflammation-related signaling pathways were significantly negatively regulated compared to those of phosphate-buffered saline-treated mice. Collectively, these findings indicated the potential of hUC-MSC to suppress immune responses in immune anomaly mediated liver disease, thus offering a potential clinical option to improve AIH.